Upaya Meningkatkan Hasil Belajar Pekerjaan Kabel dan Terminasi Menggunakan Model Quantum Teaching and Learning pada Siswa Kelas X TITL 2 SMK Negeri 6 Malang - Agung Priyadi (RC-INSTITUT, 2021)
This classroom action research aims to improve student learning outcomes through the application of the quantum teaching and learning model in the process of teaching and learning activities in the subject of Basic Electromechanical Work with the subject matter of Wiring and Termination. The research subjects were students of class X TITL 2 in the even semester of the 2019/2020 academic year of SMK Negeri 6 Malang. Researchers conducted research using two cycles of action. This classroom action research is carried out repeatedly by following predetermined cycle stages so that the objectives of the applied learning model can be achieved. Indicators of improving student learning outcomes can be seen from the increase in learning outcomes obtained by students after experiencing the process of learning activities using the quantum teaching and learning model. The results of the study stated that the application of the quantum teaching and learning model was able to improve student learning outcomes.